Hyperactivity and Pro-inflammatory Functions of Platelets in Diabetes - Jordan Greaves; Giordano Pula (Frontiers in Bioscience-Landmark)
Cardiovascular complications claim the lives of up to 70% of patients with diabetes mellitus (DM). The mechanisms increasing cardiovascular risk in DM remain to be fully understood and successfully addressed. Nonetheless, there is increasing evidence in the scientific literature of the participation of platelets in the cardiovascular complications of DM. Multiple reports describe the hyperactivity of platelets in DM and their participation in inflammatory responses. The understanding of the mechanisms underlying the contribution of platelets to cardiovascular pathologies in DM will help the development of targeted therapeutic strategies able to reduce cardiovascular risk in these patients. In this literature review, we summarise our current understanding of the molecular mechanisms leading to the contribution of platelets to cardiovascular risk in DM. Both platelet haemostatic activity leading to thrombus formation and their participation to inflammatory processes are stimulated by the biochemical conditions associated with DM. We also present evidence on how DM affect the efficacy of existing therapeutic treatments for thrombosis and, by converse, how antidiabetic drugs may affect platelet function and the haemostasis/thrombosis balance. Taken together, the growing evidence of the different and unexpected roles of platelets in the progression of DM provides a strong rationale for the design of cardiovascular drugs targeting specifically platelets, their pro-inflammatory activity and their activation mechanisms in this disease. Overall, this article provides an important up-to-date overview of the pathophysiological alterations of platelets in DM, which need to be taken into account for the effective management of cardiovascular health in this disease.